1986
DOI: 10.1037/0882-7974.1.3.220
|View full text |Cite
|
Sign up to set email alerts
|

As time goes by: Change and stability in personality over fifty years.

Abstract: Dimensions of personality, based on Q-sorted descriptions at seven points in time over a 50-year period and derived from a three-way component analysis, are described for a core sample of 118 subjects and two additional childhood samples of 99 and 108 subjects that partially overlap with the core sample. Stability and change in personality are described between adjacent periods and across a substantial segment of the life span from early childhood to late adulthood. These descriptions do not seem consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
130
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 15 publications
12
130
1
2
Order By: Relevance
“…Moreover, we predicted that the rank-order stability of traits from childhood to midlife would be lower than that found in previous studies such as Haan et al (1986) and Soldz and Vaillant (1999). This is because for the Hawaii cohort personality-trait assessments were available when the participants were in the midst of their childhood development, "middle childhood" (Shiner, 1998), and subsequently when they were in their fourth or fifth decade, when trait stability should be maximized (principles 2 and 3).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 44%
See 1 more Smart Citation
“…Moreover, we predicted that the rank-order stability of traits from childhood to midlife would be lower than that found in previous studies such as Haan et al (1986) and Soldz and Vaillant (1999). This is because for the Hawaii cohort personality-trait assessments were available when the participants were in the midst of their childhood development, "middle childhood" (Shiner, 1998), and subsequently when they were in their fourth or fifth decade, when trait stability should be maximized (principles 2 and 3).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 44%
“…Two such studies (Haan, Millsap, & Hartka, 1986;Soldz & Vaillant, 1999) are remarkable for the time span that they encompassed. For 118 participants in the Oakland Growth Study, from adolescence to mid-late adulthood, a period of approximately 50 years, Haan et al (1986) reported the following rank-order correlations for personality constructs assessed by observer Q-sorts: outgoing vs. aloof = .37; cognitively committed = .34; self-confident vs. victimized = .26; dependable = .25; assertive vs. submissive = .24; and warm vs. hostile = .14. To the extent that the first two variables are associated with Extraversion and Intellect, respectively, this suggests that those factors may be more stable than the other three of the Big Five.…”
mentioning
confidence: 99%
“…The Intergenerational Studies are considered landmark studies in human development; their history and sampling have been extensively documented elsewhere (Block, 1971;Eichorn et al, 1981;Haan et al, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…Social roles, life events, and social environments change during the life course, and such factors have been suggested as important influences on basic personality traits (Haan et al, 1986;Hogan, 1996). A number of researchers have focused on the transactions between individuals' personalities and experiences.…”
Section: Personality Changes As Person-environment Transactionsmentioning
confidence: 99%
“…McCrae and Costa's (1996) five-factor theory asserts that personality traits arise exclusively from biological causes (i.e., genes) and that they reach full maturity in early adulthood; thus, this theory predicts little or no change on any personality dimension after early adulthood. By contrast, contextualist perspectives argue that traits are multiply determined, and that one important influence on traits is the individual's social environment (Haan, Millsap, & Hartka, 1986;Helson, Jones, & Kwan, 2002). Contextualist perspectives thus predict plasticity: Change is complex and ongoing, owing to the many factors that can affect personality traits.…”
mentioning
confidence: 99%